2019
DOI: 10.1111/jan.13998
|View full text |Cite
|
Sign up to set email alerts
|

Formal and informal care after stroke: A longitudinal analysis of survivors’ post rehabilitation hospital discharge

Abstract: Aims To describe the type and the amount of formal and informal care received during the first year after home discharge and to identify the baseline predictors of the formal and informal care needs of stroke survivors. Design Longitudinal study. Data were collected between June 2013–May 2016. Methods Survivors (N = 415) were enrolled during discharge from rehabilitation hospitals and interviewed at 3 (T1), 6 (T2), 9 (T3), and 12 (T4) months. The linear mixed effects model with random intercept and random slop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 39 publications
0
30
1
1
Order By: Relevance
“…With regard to the variables significantly associated with SIS physical dimensions, we observed that stroke survivors who were younger, with hypercholesterolaemia, and who had higher physical functioning (Barthel Index) at baseline had higher strength, more ability during ADL, and higher hand function. Literature (Pucciarelli, Ausili, et al, 2019) has shown that, in order to maintain physical functioning and physical abilities, stroke survivors need to do as much physical activity as the general population. Younger stroke survivors are usually more likely to comply with this advice than the older (Alawieh et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to the variables significantly associated with SIS physical dimensions, we observed that stroke survivors who were younger, with hypercholesterolaemia, and who had higher physical functioning (Barthel Index) at baseline had higher strength, more ability during ADL, and higher hand function. Literature (Pucciarelli, Ausili, et al, 2019) has shown that, in order to maintain physical functioning and physical abilities, stroke survivors need to do as much physical activity as the general population. Younger stroke survivors are usually more likely to comply with this advice than the older (Alawieh et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 90% of stroke survivors have compromised functions (Carvalho-Pinto & Faria, 2016), which make it difficult to perform their daily life activities. By causing physical, psychological, and social disabilities, which often demand several hours per day of formal and informal assistance (Pucciarelli, Ausili, et al, 2019), adding to the financial burden on survivors and their families (Pucciarelli et al, 2020), stroke decreases individuals' quality of life (QoL; Donkor, 2018). Multiple risk factors, including age, gender (Bushnell et al, 2014), dependency in activities of daily living (ADL; Kim et al, 2014), social support (Elloker & Rhoda, 2018), and depression (Pucciarelli et al, 2017), have been associated with poorer QoL in stroke survivors.…”
Section: Introductionmentioning
confidence: 99%
“…Marital status was also a significant factor for living at home up to two years after discharge [62,63], while social support was associated with community reintegration at three months postdischarge [64]. This indicates that the need for support exists beyond inpatient rehabilitation [65]. Additionally, the influence of ethnicity was assessed in the USA.…”
Section: Discussionmentioning
confidence: 99%
“…2 A literatura é unanime em demonstrar que os sobreviventes apresentam inúmeras sequelas crónicas levando a uma diminuição na autonomia destes doentes e obrigando à presença de um cuidador para auxílio nas atividades de vida diária e na gestão das rotinas da vida após um AVC. 3 A solução mais frequente no apoio a estes doentes passa pela presença de um cuidador informal (CI) no domicílio que não tem formação no que diz respeito às sequelas de AVC ou dos cuidados necessários/adequados para estes doentes. 4 O CI é a pessoa da rede social do doente, não remunerada, com relação significativa (familiar, parceiro (a), amigo(a) e/ou vizinho(a)), que se assume como o principal responsável pela organização, assistência e/ou prestação de cuidados.…”
Section: Introductionunclassified